The effect of pharmacy information management system on safety medication use: A study from private hospitals in İstanbul - Mumcu, Gonca (Marmara Pharmaceutical Journal, 2014)
Pharmacies located in hospitals are important units for the healthcare system. The aim of the study was to evaluate pharmacy information management system (PIMS) in the perspective of patient safety in private hospitals. In the study, PIMS related with medication safety and communication among health professionals and global patient safety were evaluated by manager pharmacists (n=104) working in private hospitals. Data was collected by the questionnaire for PIMS functions related with medication safety and communication among health professionals in the perspective of patient safety. In linear regression analysis, four items regarding “clinical warning system about medication interactions”, “supporting collaboration between physician and pharmacists”, preventing prescribing errors” and “increasing in reliability of patient’s data” were found to be predictive factors for patient safety in PIMS Consequently, a PIMS improves patient safety by preventing medication error.
Keywords: Pharmacy information management system, patient safety, private hospitals